Who Needs Foreign Banks? - Daniel Gros (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper shows that countries with weak banking system and fiscal institutions, should benefit from the presence of foreign banks, which can constitute a commitment and transparency device. Foreign banks can also reduce the probability of self-fulfilling speculative attacks. A strong presence of foreign banks can make a currency peg feasible in the first place by rendering it more resistant to speculative attacks. The European experience is instructive in this respect. In all the 10 countries from Central and Eastern Europe (CEEC) that will join the EU in 2004/7 the banking system is now dominated by foreign banks.
Keywords: 330